Effects of nitrogen deposition, drought and their interaction, on functional and structural traits of Fraxinus ornus L. and Quercus ilex L. (2nd January 2017) - Fusaro, L.; Salvatori, E.; Manes, F.
Abstract: A controlled experiment was conducted in order to understand how functional and structural traits of species with different leaf habits ( Fraxinus ornus and Quercus ilex ) shift as a consequence of nitrogen (N) addition (30 kg ha yr −1 ) and to explore the effect that N has on the water stress response. The experiment was divided in two stages: stage I, N addition under well-watered condition; stage II, N addition under drought. Functionality of the photosynthetic machinery, growth and biomass partitioning were assessed. The N content at leaf level increases in F. ornus only, which invests resources on photosynthetic machinery, whereas Q. ilex tends to store N in non-photosynthetic biomass, increasing relative growth rate and biomass, resulting in different allometric ratio. This effect may play a role in water stress response. Stomatal conductance of Q. ilex treated with N and subjected to water stress is lower relative to drought treatment. On the contrary, F. ornus takes advantage of N addition that has ameliorative effects on its functionality when drought was imposed. The obtained results, highlighting response mechanisms to multiple stress factors, should help to better understand and assess the performance of forest ecosystems under the foreseen environmental changes.